Uji Kinerja Fotokatalis Komposit Tio2-Graphene (Cocopas) Untuk Degradasi Fenol - Fadhila Ulfa; Desi Heltina; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Phenol is a chemical compound that is one of the hazardous industrial wastes. An excessive concentration of phenol can cause damage in the environment and human life. Phenol removal can be done by photocatalysis process using photocatalyst materials such as titanium dioxide (TiO2).TiO2 was composited with graphene to increase the photocatalytic activity of TiO2. Graphene was modified with cocoPAS before to disperse graphene when composited with TiO2. TiO2-Graphene (cocoPAS) composite was characterized by SEM. Based on the results of characterization, it can be seen that TiO2 particle loaded on the graphene sheet which indicates that the composites have been successfully made. The performance of the TiO2-Graphene (cocoPAS) composite in phenol degradation was tested in a photocatalysis process for 4 hours. A variable in this photocatalysis process is photocatalysis temperature (40 and 50 oC). the most effective TiO2-Graphene (cocoPAS) composite performance was achieved when the photocatalysis temperature is 50 oC, which can degrade phenol by 97% in 4 hours.Keywords: CocoPAS , degradation, photocatalysis, phenol, graphene, titanium dioxide